UMP receives RM63,650 research grant for Pahang State Pondok School Education System - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 12 October 2022 - Universiti Malaysia Pahang (UMP) received a Research Grant for the Empowerment and Recognition Initiative of the Pahang State Pondok School Education System amounting to RM63,650 from the Pahang Islamic Religious and Malay Customs Council (MUIP).